Komunikasi interpersonal antara pelatih dengan murid beladiri jujitsu indonesia di dojo wijaya putra surabaya - Cristoper Prawira Sinaga; Iwan Joko Prasetyo (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2020)
Jujitsu or known as IJI (Institute of Jujitsu Indonesia) is one of a branch of martial arts in Indonesia. In training Jujitsu is needed of a communication to explain and train the students. I don't know that communication, interpersonal or in groups. Dojo (Training Place) Wijaya Putra Surabaya is a place to practice with various kinds of people, whether it's from a wide range of rates ranging from sabang to merauke, a wide range of religion, a wide range of ages. With a variety of such differences can be seen how interpersonal communication that will be among the coaches and students at the arena that will cause some comparisons between one and others. The research is a research a qualitative descriptive, The use of research sort of descriptive set of qualitative is the right method to find out the results of research that aims to find out how interpersonal communication by coach to students with a way to explain using a reality so that the study be something definite. The results can be found by using the Social Penetration theory which has 4 stages, namely, orientasi, exploratory affective stage, affective stage, stable stage. Of those 5 (five) subject of three has reached the stage stable while two other reached the affective stage. Because a coach doing the first approach to the students it in a way to tell the history of training, joking and personal life so that the stable in the study. The subjects based on Purposive Sampling and data retrieval using Depth interview.